(untitled) (Proceedings of International Conference on Scientific Research in Natural and Social Sciences, 2024)
In this paper, we consider the solvability and unsolvability of solutions of a nonlinear diffusion system with a source and nonlinear boundary conditions in the case of slow diffusion. Establishing numerous self-similar super-solutions and sub-solutions for the nonlinear diffusion system.